Creativity in Islamic entertainment: a case study of Malaysian nashid groups (Rabbani, Raihan and Hijjaz) = Kreativiti dalam hiburan Islam: kajian kes kumpulan nasyid Malaysia (Rabbani, Raihan and Hijjaz) - Zaroum, AbdulHamid Mohamed Ali; Abdul Razak, Mohd Abbas; Abdul Razak, Abdul Latif (IIUM Press, International Islamic University Malaysia, 2018)
This paper attempts to shed some light on Islamic Nasyid groups in Malaysia, in particular RABBANI, RAIHAN AND HIJJAZ. With the emergence of globalization and its entertainment aspect, and due to the huge influence of modernization on the society especially among the youth, there was, indeed, a need for an alternative entertainment. And, as far as Muslims are concerned, the most effective way in this regard was, to a great extent, Islamic Nasyid. Entertainment itself has been an area of great discussion and dispute among Muslim scholars throughout the ages all over the world. In Malaysia, the issue of allowing or disallowing entertainment specifically songs and music is no longer a big issue. As a matter of fact, entertainment is part of the traditions and culture of the Muslims in this part of the world. Nevertheless, the major concern here is that what kind of songs and music do Nasyid groups present? Could Islamic Nasyid be an alternative to the conventional or non-Islamic songs? Is it possible for Nasyid performance to be viewed as an act of worship? To what extent Nasyid groups are contributing in the Islamization of entertainment and enhancement of Islamic awareness in Malaysian society?? The focus of this research will be on: (1) The historical background of RABBANI, RAIHAN AND HIJJAZ Nasyid groups (2) The role these groups have been playing in creating Islamic awareness; (3) The Islamization of songs and music as promoted by these three groups; (4) The challenges these Nasyid groups are facing in terms of publication and audience attendance etc.; and (5) The future of Islamic Nasyid in Malaysia. This research is expected to provide important findings that will enhance Islamic awareness among the society members. Besides, it is hoped that this paoer will highlight the effectiveness of Islamic Nashyd in Malaysia especially in this borderless globalized village. ********************************************************** Makalah ini cuba menerangkanbeberapa kumpulan NasyidIslam di Malaysia, khususnya RABBANI, RAIHAN DAN HIJJAZ. Dengan kemunculan globalisasi dan aspek hiburannya, dan disebabkan oleh pengaruh besar pemodenan terhadap masyarakat terutama kalangan belia, hiburan alternatif amatlahdiperlukan.Cara yang paling berkesan dalam hal ini adalah, sebahagian besarnya, NasyidIslam. Hiburan itu sendiri merupakanbidang perbincangan dan pertikaian hebat di kalangan para ulama Islam sepanjang zaman di seluruh dunia. Di Malaysia, isu membenarkan atau menolak hiburan khususnyalagu dan muzik tidak lagi menjadi masalah besar. Hakikatnya, hiburan adalah sebahagian daripada tradisi dan budaya umat Islam. Walau bagaimanapun, kebimbangan utama di sini,apakah jenis lagu dan muzik yang didendangkan oleh kumpulan Nasyidtersebut? Bolehkah NasyidIslam menjadi alternatif kepada lagu konvensional atau yang bersifat tidak Islamik?Adakah mungkin Nasyiddilihat sebagai satu ibadah? Sejauh manakahkumpulan Nasyidmenyumbang kepadaIslamisasi hiburan dan meningkatkankesedaran Islam dalam masyarakat Malaysia? Fokus penyelidikan ini adalah: (1) latar belakang kumpulan-kumpulan NasyidRABBANI, RAIHAN DAN HIJJAZ (2) Peranan kumpulan-kumpulan ini dalammembentuk kesedaran Islam; (3) Islamisasilagu dan muzik seperti yang diketengahkanoleh ketiga-tiga kumpulan ini; (4) Cabaran yang dihadapi kumpulan-kumpulanNasyidinidari segi penerbitan dan menarik minat pendengar; dan (5) Masa depan NasyidIslam di Malaysia. Penyelidikan ini dijangka memberikan penemuan pentingyang akan meningkatkan kesedaran Islam di kalangan masyarakat. Di samping itu, diharapkan makalah ini akan menonjolkankeberkesanan Nashyd Islam di Malaysia terutamanya dalam dunia globalisasi tanpa sempadan.